HOW BILINGUAL PROGRAM HELPS STUDENTS IMPROVE THEIR COMMUNICATIVE COMPETENCE - Susie Kusumayanthi; Sisca Debora Stevanie (Universitas Widyatama, 2021)
Bilingual program is a program that combines two languages, in this context are English-Indonesian, into a learning program in school. This bilingual program includes not only theory-based learning but also practice-based learning. Bilingual program can influence students in many ways, including in their communicative competence. The aim of this research is to find out that whether bilingual program can help students improve their communicative competence and how the students deal with it. Qualitative descriptive as the method of research and with observation, interviews, and document analysis/data analysis as the data collection techniques. This research shows that it is true that bilingual program can influence the students in their communicative competence. Based on this result, it can be concluded that bilingual program can help students improve their communicative competence with the programs held by school.